Financial constraints and the decision to lease: Evidence from German SME - Constantin Slotty (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2009)
The objective of this paper is to test the hypothesis that in particular financially constrained firms lease a higher share of their assets to mitigate problems of asymmetric information. The assumptions are tested under a GMM framework which simultaneously controls for endogeneity problems and firms' fixed effects. We find that the share of total annual lease expenses attributable to either finance or operating leases is considerably higher for financially strained as well as for small and fast-growing firms those likely to face higher agency-cost premiums on marginal financing. Furthermore, our results confirm the substitution of leasing and debt financing for lessee firms. However, we find no evidence that firms use leasing as an instrument to reduce their tax burdens.
Keywords: D23; D92; C23; 330; Leasing; financial constraints; capital structure; asymmetric information; Finanzierungsleasing; Verschuldungsrestriktion; Kapitalstruktur; Asymmetrische Information; Klein- und Mittelunternehmen; Unternehmenswachstum; Deutschland